Plasticity after pediatric cochlear implantation: Implication from changes in peripheral plasma level of BDNF and auditory nerve responses. (February 2018) - Alemi, Razieh; Motassadi Zarandy, Masoud; Joghataei, Mohammad Taghi; Eftekharian, Ali; Zarrindast, Mohammad Reza; Vousooghi, Nasim
Abstract: Introduction: Sensory neural hearing loss could lead to some structural and physiological changes in the auditory pathways, such as alteration in the expression of neurotrophins. These factors, especially Brain-Derived Neurotrophic Factor (BDNF), play an important role in synaptic functions and experience-related plasticity. Restoring cochlear function after hearing loss is possible through cochlear implantation (CI). Evaluation of the blood concentration changes of neurotrophins as prerequisites of plasticity could help scientists to determine the prognosis of CI as in the candidacy procedure or enhancing prosthesis function by adding the exact needed amount of BDNF to the electrode array. Methods: Here we have studied the plasma BDNF concentration before CI surgery and 6 months after using CI device in 15 pediatric CI recipients and compared this level with changes of BDNF concentration in 10 children who were using hearing aid (H.A). In addition, we searched for a possible correlation between post-surgery plasma BDNF concentration and electrical compound action potential (ECAP) and comfort-level (C-level) thresholds. Results: Plasma BDNF concentration in children with CI increased significantly after CI surgery, while this difference in H.A group was not significant. Analysis of repeated measures of ECAP and C-level thresholds in CI group showed that there were some kinds of steadiness during follow- up sessions for ECAP thresholds in basal and E16 of middle electrodes, whereas C-level thresholds for all selected electrodes increased significantly up to six months follow-up. Interestingly, we did not find any significant correlation between post-surgery plasma BDNF concentration and ECAP or C-level threshold changes. Conclusion: It is concluded that changes in C-level threshold and steady state of ECAP thresholds and significant changes in BDNF concentration could be regarded as an indicator of experienced-related plasticity after CI stimulation.